Komodifikasi Banten Di Desa Pejaten, Kecamatan Kediri, Kabupaten Tabanan - Cupu Tyasningrum, I Gst. Ayu Agung; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
The Balinese Hinduism community performs religious ceremonies using a means called banten, banten as a means of religious ceremony to accompany every ceremony in the daily life of Balinese Hinduism community. Banten is made in a cooperative manner by the Balinese Hinduism community, but the emergence of thought and efficiency in society makes banten as consumer goods (commodity) that are traded by certain parties then known by the term commodification. Banten commodification caused by several things due to knowledge and skill, limited time and effort, economic limitation and strong market ideology. Banten commodification happened by the process which covering production, distribution, and consumption process. Then, banten commodification have the impact on the social, cultural, economic and material. Keywords: banten, commodification, market ideology.